2017
DOI: 10.1007/s00203-017-1356-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial diversity associated with bioremediation of used lubricating oil in tropical soils

Abstract: Used lubricating oil (ULO) is a widespread contaminant, particularly throughout tropical regions, and may be a candidate for bioremediation. However, little is known about the biodegradation potential or basic microbial ecology of ULO-contaminated soils. This study aims to determine the effects of used lubricating oil (ULO) on bacterial community structure and diversity. Using a combination of culture-based (agar plate counts) and molecular techniques (16S rRNA gene sequencing and DGGE), we investigated change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…We found that addition of lubricants at the assessed concentration did not induce remarkable impact on the soil microbiome: phylogenetic profile of control soil did not dramatically differ from treated soils after the biodegradation process has occurred. Proteobacteria was particularly abundant in the grease-spiked soils compared to the untreated sample, which is consistent with previous studies that have reported Proteobacteria as major phylum in soils added of used oil lubricants or hydrocarbon-containing soils [ 31 ]. In this context, CL soil showed an increased percentage of γ -Proteobacteria , which includes many hydrocarbon-degrading genera as Pseudomonas .…”
Section: Discussionsupporting
confidence: 91%
“…We found that addition of lubricants at the assessed concentration did not induce remarkable impact on the soil microbiome: phylogenetic profile of control soil did not dramatically differ from treated soils after the biodegradation process has occurred. Proteobacteria was particularly abundant in the grease-spiked soils compared to the untreated sample, which is consistent with previous studies that have reported Proteobacteria as major phylum in soils added of used oil lubricants or hydrocarbon-containing soils [ 31 ]. In this context, CL soil showed an increased percentage of γ -Proteobacteria , which includes many hydrocarbon-degrading genera as Pseudomonas .…”
Section: Discussionsupporting
confidence: 91%
“…The presence or absence of nutrients in the process of bioremediation have been associated with the increase of microbial population and moderation of nutrients and other physicochemical parameters of the soil. According to Meeboon et al (2018) finding supporting the presence of nutrients as a key factor that may also affect the microbial population during a treatment process. The application of exogenous nutrients which attached to the soil fraction could serve as limiting nutrients through slow-release ( Khadem & Raiesi, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…Proteobacteria are copiotrophs thus their signi cant increase during remediation is in response to the addition of nutrients to the oilpolluted soil. Also, several species of this phylum are established hydrocarbon degraders [7,45] and may have increased in relative abundance due to more favourable environmental conditions during remediation. Meanwhile, Cyanobacteria are photosynthetic microorganisms that exist in diverse environments and are known to quickly adapt to uctuating environmental nutrient conditions [46,47].…”
Section: Discussionmentioning
confidence: 99%